Prevalence of Aerobic Bacterial Vaginosis and Trichomonas Vaginalis Associated with Socioeconomic Factors among Women in Misan Governorate.. - Zahrah Adnan1, Huda Dhaher2, Mohammed F. Marjani3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Vagina is an ecosystem balance, human vagina is dominated by lactobacillus spp which creates a vaginal acidity environment(3.8-4.5) to protect vagina from Vaginitis pathogen .Vaginitis is an inflammation of vagina caused by bacterial vaginosis and Trichomonas vaginalis . The aims of this study was investigated aerobic bacterial vaginosis , lactobacillus spp. and T.V in women with vaginitis. Study the clinical feature and demographic factors with vaginitis . 345 samples were collected from women with vaginitis. Study a demographic variables such as age , education level, socioeconomic state , residence, parity , in pregnant and non-pregnant women .